2016
DOI: 10.1007/s10802-016-0226-9
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder, Trait Impulsivity, and Externalizing Behavior in a Longitudinal Sample

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is highly comorbid with and predictive of externalizing behavior, yet is most often examined categorically, not dimensionally. We tested a recently proposed trait impulsivity model by dimensionally examining measures of childhood inattention and hyperactivity/impulsivity separately as predictors of later externalizing behavior in an all-female longitudinal sample of 228 young women. We also examined influences of parenting and peer relations, given the transactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 67 publications
(97 reference statements)
1
43
0
1
Order By: Relevance
“…Many other studies confirmed impulsivity served as the key trait in externalizing disorders. Also, among ADHD symptoms, hyperactive/impulsive symptoms are known to predict the externalizing behavior in teens and adults, while inattention has not 8). Another study reported the increase in impulsivity could add to the risks of ADHD in childhood and AUD in adulthood, indicating the impulsivity was a factor underlying the correlation between AUD and externalizing disorders including ADHD 32)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other studies confirmed impulsivity served as the key trait in externalizing disorders. Also, among ADHD symptoms, hyperactive/impulsive symptoms are known to predict the externalizing behavior in teens and adults, while inattention has not 8). Another study reported the increase in impulsivity could add to the risks of ADHD in childhood and AUD in adulthood, indicating the impulsivity was a factor underlying the correlation between AUD and externalizing disorders including ADHD 32)…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we focused on the motor impulsivity, which is the core trait of externalizing disorders. Longitudinal research on externalizing behavior found the hyper-active/impulsive trait of ADHD predicted the externalizing behavior in teens and young adults 8). Another study mentioned the impulsivity, or behavioral impulsivity in particular, was the core symptom of the externalizing spectrum 15).…”
Section: Introductionmentioning
confidence: 99%
“…Dalley and Robbins 2017), attention-deficit hyperactivity disorder (Ahmad andHinshaw 2017, Martel et al 2017), antisocial personality disorder (González et al 2016, Martel et al 2017, and bipolar disorder (Tu et al 2017), this finding supports the notion that the beneficial effects of nature may be especially evident in those individuals who possess greater vulnerability to mental-health issues. The implications of these results are twofold.…”
Section: Associations Between Momentary Mental Well-being Score In mentioning
confidence: 72%
“…One of the aims of our project was to explore how the impact of the surrounding built environment on the mental well-being of an individual might depend on their vulnerability to developing mental-health issues. For this reason, we included an assessment of trait impulsivity, a well-established psychological measure of one's tendency to behave with little forethought, reflection, or consideration of the consequences (Mayhew and Powell 2014 (Ahmad andHinshaw 2017, Martel et al 2017), antisocial personality disorder (González et al 2016, Martel et al 2017, and bipolar disorder (Tu et al 2017). We used the data to test three related hypotheses: (1) exposure to natural features, including trees, the sky, birdsong, and water, would be associated with higher levels of momentary mental wellbeing; (2) these effects would still be evident in subsequent assessments, in which people are no longer exposed to trees, the sky, birdsong, and water, indicating time-lasting benefits;…”
Section: The Urban Mind Toolmentioning
confidence: 99%
“…In turn, rejection sensitivity increases the likelihood of retaliation [61]. Given that disorganized schizotypy also features lack of concentration and attentional deficits [62], it may be interesting to explore disorganized schizotypy in relation to attention deficit hyperactivity disorder which has been linked to antisocial behavior through inattention and impulsivity [63].…”
Section: The Path From Disorganized Schizotypy To Depression and Aggrmentioning
confidence: 99%